Examining the Nutritional Quality of Canadian Packaged Foods and Beverages with and without Nutrition Claims - Franco-Arellano, Beatriz (Nutrients, 2018)
Nutrient content claims, health claims, and front-of-pack symbols (henceforth referred to as “nutrition claims” in the present study) are often found on food labels in Canada. However, it is currently unknown whether foods and beverages (F&Bs) carrying nutrition claims have a more favourable nutritional profile than those without such claims. This study examined differences in the global nutritional quality, as determined by the Food Standards Australia New Zealand Nutrient Profiling Scoring Criterion (FSANZ-NPSC), of Canadian F&B bearing nutrition claims as compared to those without, as well as in their nutritional composition. Data (n = 15,184) was obtained from the University of Toronto 2013 Food Label Information Program. Forty-two percent of F&Bs carrying nutrition claims (n = 2930/6990) were found to be ineligible to carry claims based on the FSANZ-NPSC, in comparison to 66% of F&Bs without (n = 5401/8194, p < 0.001). Sugars and sweets, and miscellaneous products were the food categories with larger proportions of foods carrying nutrition claims not meeting the FSANZ-NPSC eligibility criteria. F&Bs with nutrition claims had fewer calories, less saturated fat, sodium, and sugar, and higher content of protein and fibre than comparable products without nutrition claims (p < 0.05 in all cases). In conclusion, nearly half of F&Bs carrying nutrition claims in Canada did not meet the FSANZ-NPSC threshold, although Canadian products carrying nutrition claims have an overall “healthier” profile than their counterparts without such claims.